PGR Gene Fusions Identify a Molecular Subset of Uterine Epithelioid Leiomyosarcoma With Rhabdoid Features. (June 2019) - Chiang, Sarah; Samore, Wesley; Zhang, Lei; Sung, Yun-Shao; Turashvili, Gulisa; Murali, Rajmohan; Soslow, Robert A.; Hensley, Martee L.; Swanson, David; Dickson, Brendan C.; Stewart, Colin J.R.; Oliva, Esther; et al.
Abstract : Genetic aberrations among uterine epithelioid leiomyosarcomas are unknown. Following identification of an index case with NR4A3-PGR fusion demonstrating monomorphic morphologic features, we interrogated additional uterine tumors demonstrating similar histology and sought to describe the morphologic and immunohistochemical characteristics of PGR -rearranged sarcomas. Targeted next-generation RNA sequencing was performed on RNA extracted from formalin-fixed paraffin-embedded tissue of the index case. Fluorescence in situ hybridization using custom probes flanking PGR and NR4A3 genes was applied to 17 epithelioid leiomyosarcomas, 6 endometrial stromal tumors, and 3 perivascular epithelioid cell tumors. NR4A3-PGR fusion (n=4) and PGR rearrangement (n=2) were detected in 6 (35%) epithelioid leiomyosarcomas. Median patient age was 45 years, and all presented with FIGO stage I or II tumors, 2 being alive with disease at 75 and 180 months. All tumors were centered in the cervical stroma or myometrium and consisted of cells with abundant eosinophilic cytoplasm (epithelioid), including many displaying dense intracytoplasmic inclusions (rhabdoid). Myxoid matrix and hydropic change imparted a microcystic growth pattern in 4 tumors. Five also showed a minor spindle cell component which was low-grade in 3, consisting of bland spindle cells with low mitotic activity. High-grade spindle cell morphology was seen in 2 tumors, exhibiting a storiform pattern of atypical spindle cells associated with brisk mitotic activity. Desmin, estrogen receptor, and progesterone receptor were positive in all 6 tumors, while CD10 and HMB45 were negative. PGR rearrangements define a genetic subset of epithelioid leiomyosarcomas with often biphasic morphology consisting of epithelioid and rhabdoid as well as spindle cell components. Abstract : Supplemental Digital Content is available in the text.